2012
DOI: 10.2174/156652312802762554
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Gene Electrotransfer Process: Evidence for the Involvement of the Plasmid DNA Topology

Abstract: Electropermeabilization is a non-viral method that can be used to transfer plasmid DNA (pDNA) into cells and tissues. According the applications and considered tissues, this safe method can be less efficient than the viral approaches. Biophysical mechanisms of gene electrotransfer are not entirely known. Contrary to small molecules that have direct and fast access to the cytoplasm, pDNA is electrophoretically pushed towards the permeabilized membrane where it forms a complex before being transferred into the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…Assuming a Poisson distribution for the formation of LMDS within the population of plasmids (data not shown), at 100 Gy 18% of the irradiated plasmids have one LMDS per plasmid, while only 2% of the plasmids are not functional. There are contradictory conclusions in the literature concerning the effects of plasmid topology on transformation efficiency (98)(99)(100)(101), however our results in Fig. 4 clearly show that the transformation efficiency initially increases with dose, reaching a maximum at about 200 Gy.…”
Section: Discussioncontrasting
confidence: 69%
“…Assuming a Poisson distribution for the formation of LMDS within the population of plasmids (data not shown), at 100 Gy 18% of the irradiated plasmids have one LMDS per plasmid, while only 2% of the plasmids are not functional. There are contradictory conclusions in the literature concerning the effects of plasmid topology on transformation efficiency (98)(99)(100)(101), however our results in Fig. 4 clearly show that the transformation efficiency initially increases with dose, reaching a maximum at about 200 Gy.…”
Section: Discussioncontrasting
confidence: 69%
“…In mouse lyoma cells, electroporation in the presence of linear DNA reached higher level of transfection in comparison to cells electroporated with circular DNA. Following investigations in bacterial and mammalian cells, using two or three DNA isomers (linearized, circular supercoiled or circular relaxed DNA), showed that circular DNA, rather than linear DNA, is optimal for successful gene electrotransfer [169, 331, 332]. These studies revealed that DNA interaction with the membrane is not dependent on its topological isometry but DNA expression is significantly lower for linearized DNA.…”
Section: Gene Electrotransfermentioning
confidence: 99%
“…In bacterial cells, Xie et al observed a lower stability of the linear DNA, which is interpreted as a rapid degradation by intracellular enzymes [332]. Based on DNA geometry and stiffness, one can suggest other hypotheses [331]. Since circular DNA has a more congealed form and a bigger diameter than linear DNA (20-30 nm vs. 2-3 nm), its electrophoretic migration could be more efficient and/or increase the size/lifetime of membrane defects (pores) or cause larger membrane invaginations near the absorbed DNA.…”
Section: Gene Electrotransfermentioning
confidence: 99%
“…These data indicate that even longterm storage of naked plasmid DNA at controlled conditions of -20°C preserves the plasmid topology as long as for 7 years and prevents the plasmid from degradation. This is of primary importance when plasmid DNA is used for gene therapy studies because it has been shown that ccc forms of plasmid DNA are required for effective gene transfer compared with oc or linearized forms (Remaut et al, 2006;Tolmachov, 2009;Escoffre et al, 2012).…”
Section: Analyses Of Plasmid Dna Topologies By Cge and Agementioning
confidence: 99%